Integrated nutrient management module to improve productivity and economics of short grain aromatic rice (Oryza sativa)- greengram (Vigna radiata) sequence - MANGARAJ, S; PAIKARAY, R K; GARNAYAK, L M; PRADHAN, S R; BEHERA, S D (The Indian Journal of Agricultural Sciences, 2023)
The present field study was carried out during 2017–18 and 2018–19 rainy (kharif) and winter (rabi) seasons in order to examine the impact caused by integrated nutrient management (INM) on the yield and quality of the short grain aromatic rice (Oryza sativa L.)-greengram (Vigna radiata L.) combination. Two years experimental data concluded that integration of 50% recommended dose (RD) as fertilizer + 50% RD of nitrogen via farm yield manure (FYM) resulted in considerably higher economic yield (3837.1 and 3917.7 kg/ha) of short grain aromatic rice cv. Nua Acharamati which were at par with 75% RD as fertilizer + green manuring of dhaincha (3438.5 and 3539.1 kg/ha). Pooled data revealed that, residual effect of 50% RD as fertilizer + 50% RD of nitrogen (FYM) and 75% RD as fertilizer + Rhizobium + PSB in greengram recorded the highest number of pods/plant (18.2), seeds/pod (11.3), pod length (9.3 cm), test weight (32.7 g), seed yield (925.7 kg/ha) and stover yield (2240.7 kg/ha) in greengram cv. IPM-02-03. Application of 50% RD as fertilizer + 50% RD of nitrogen (FYM) to aromatic rice recorded the highest hulling recovery (75.8 and 75.5%), milling recovery (68.0 and 68.3%), head rice recovery (60.0, 59.7%) and crude protein content (8.75 and 9.11%) during both of the years experiment being at par with application of 75% RD as fertilizer + green manuring. Economics of the system revealed the highest gross return, net return and B:C ratio by application of 50% RD as chemical fertilizer + 50% RD of nitrogen (FYM) in rice followed by 75% RD as chemical fertilizer + Rhizobium + PSB in greengram.